Study on detonation characteristics of pulverized coal and evolution law of detonation residue - Jing Guo; Shirong Ge; Yinan Guo; Jiayu Liang; Ruibo Yang (Scientific Reports, 2024)
Abstract This study explores the detonation characteristics and compositional changes of pulverized coal, focusing on its use in Rotary Detonation Wave (RDW) technologies. While pulverized coal has shown high fuel efficiency in RDW settings, transitioning from theory to practical detonation engineering presents substantial scientific and technical hurdles. A key issue is the reprocessing of detonation byproducts for in-situ coal mine gob filling, a topic that has received little attention. Utilizing advanced methods like X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR), this paper investigates the micro-morphology, composition, and aromatic structures of gas–solid products pre and post-detonation at the Tashan Coal Mine's 2305 working face. Results indicate that coal dust from the underground mining face has enhanced detonation characteristics, with the addition of coal powder fuel extending the gas detonation limits. This benefits economic aspects by reducing reliance on gas fuel and lowering detonation fuel costs. The highest recorded detonation wave velocity was 2450 m/s, 14.8% greater than that of coal dust from external sources, suggesting more effective energy release and pressure gain. Furthermore, the study links detonation combustion intensity to coal's aromatic properties, noting a post-detonation aromaticity index (I) of 0.4941. This indicates an improvement in the aromatic structure under high-temperature conditions, vital for coal's reactivity and energy efficiency in RDW applications. This research not only deepens the understanding of coal dust combustion mechanisms but also advances clean coal utilization and deep coal fluidization mining, addressing significant RDW technological challenges.